Hubungan Kontrol Diri dengan Adiksi Internet pada Mahasiswa - Fifi Siti Fauziah Yani; Andri Nurmansyah (Jurnal Health Sains, 2022)
Today's advanced technology and can provide convenience for its users, one of which is the internet. The longer attachment to the internet will form a habit called internet addiction. In addition, internet addiction also has a negatif impact on both physical and mental health. Unwise use of the internet cannot be separated from the self-control of the individual who uses it. Self control is an individual's ability to control unexpected behavior. This study used a descriptive analytic design with a cross sectional approach. The questionnaire used was the Indonesian version of the Internet addiction Test (IAT) in testing internet addiction behavior and the self-control questionnaire in testing self-control. It was found that the value of Sig. (2-tailed) between Internet addiction and Self control is 0.002 < 0.05, which means that there is a significant relationship between the Self control and Internet addiction variables. Based on the results of research and discussion on the relationship between self-control and internet addiction in students, it can be concluded that there is a relationship between self-control and internet addiction in college students.